Sphingosine 1-phosphate axis: a new leader actor in skeletal muscle biology - Donati, Chiara; Cencetti, Francesca; Bruni, Paola (Frontiers in Physiology, 2013)
Sphingosine 1-phosphate (S1P) is a bioactive lipid involved in the regulation of biological processes such as proliferation, differentiation, motility and survival. Here we review the role of S1P in the biology and homeostasis of skeletal muscle. S1P derives from the catabolism of sphingomyelin and is produced by sphingosine phosphorylation catalyzed by sphingosine kinase. S1P can act either intracellularly or extracellularly through specific ligation to its five G protein-coupled receptors named S1P receptors (S1PR). Many experimental findings obtained in the last 15 years demonstrate that S1P and its metabolism play a multifaceted role in the regulation of skeletal muscle regeneration. Indeed, this lipid is known to activate muscle-resident satellite cells, regulating their proliferation and differentiation, as well as mesenchymal progenitors such as mesoangioblasts that originate outside skeletal muscle, both involved in tissue repair following an injury or disease. The molecular mechanism of action of S1P in skeletal muscle cell precursors is highly complex, especially because S1P axis is under the control of a number of growth factors and cytokines, canonical regulators of skeletal muscle biology. Moreover, this lipid is crucially involved in the regulation of skeletal muscle contractile properties, responsiveness to insulin, fatigue resistance and trophism. Overall, on the basis of these findings S1P signalling appears to be an appealing pharmacological target for improving skeletal muscle repair. Nevertheless further understanding is required on the regulation of S1P downstream signalling pathways and the expression of S1PR. This article will resume our current knowledge on S1P signalling in skeletal muscle, hopefully stimulating further investigation in the field, aimed at individuating novel molecular targets for ameliorating skeletal muscle regeneration and reducing fibrosis of the tissue after a trauma or due to skeletal muscle diseases.